Imigração e envelhecimento em São Paulo: perfil de um grupo de idosos coreanos - Hong, Hee Jeung (2010)
The history of the first Korean immigrants in Brazil has as its official landmark the date of February 12, 1963. Today, it is estimated that the country has a population of 50 thousand Koreans. São Paulo was the city they elected. Nowadays, it houses approximately 90% of the Korean community. However, there is no research into the Korean elderly people in Brazil. This quantitative study aims to outline the profile of a group of Korean elderly immigrants who live in the city of São Paulo, drawing a comparison between men and women. A semi-structured questionnaire was administered with closed and one open question, and multiple choice answers. A total of 167 subjects participated in this investigation: 120 women and 35 men (12 did not answer the item sex ). All of them were older than 60 years and were designated by leaders of Evangelical churches, of the Catholic Church and by people belonging to the social network of the researcher, who is a member of the Korean community. Among the collected data, we verified the longevity of the Korean elderly individuals, as a large part of them are aged between 70 and 79 years (44%) and between 80 and 85 years (35%). Of the subjects, 59.2% were widows and only 18.2% were widowers, which demonstrates the feminization of old age in the Korean community. Concerning the time they have been living in the city of São Paulo, we found that 38% of the participants have been living in the metropolis for 36 to 45 years; that is, they arrived at the city between the years of 1965 and 1974, in the great migratory current, and the largest flow was in the 1970s. Population s aging was the demographic phenomenon of the 20th century. Thus, it has become imperative to think about policies and actions targeted at the elderly, so that autonomy and independence can be preserved, and to reflect on the inclusion of this population in health promotion programs and disease prevention policies, despite the language barrier, a strong impeding factor. The collected data contribute to the formulation of guidelines for comprehensive social and educational actions, informative and inclusive, to the community of Korean elderly people, who exclude themselves from the programs directed to the elderly population in Brazil, due to lack of knowledge and difficulty in communication. In addition, they contribute to promote solidarity and actions that improve the quality of life of the immigrants settled in the city of São Paulo, in view of the fact that in 2013 the community will complete 50 years of immigration